(untitled) (Journal of Applied Oral Science, 2022)
There is a lack of clinical evidence on mandibular overdentures (MOD) supported by a single implant. Objective: To compare patient satisfaction and masticatory performance in MOD supported by one versus two implants in a two-group parallel randomized clinical trial. Material and Methods:Twenty-one patients wearing new maxillary and mandibular complete dentures (CDs) were randomly divided to receive one (GI, n = 11) or two (GII, n = 10) implants in the mandibular arch. Four months after implant placement, o-ring abutments were installed in the implants, and matrix attachments were placed in the lower complete dentures. Patient satisfaction with their dentures and masticatory performance were compared at baseline, 3, 6, and 12 months after the procedure. Data on patient satisfaction were analyzed using the Friedman test and the Mann-Whitney U test. Data on masticatory performance were analyzed using one-way repeated measures analysis of variance (ANOVA) and Student's t test (α=0.05). Results: Both groups exhibited a significant increase in overall patient satisfaction in all periods evaluated (p<0.05), except for GI after 12 months, which had values similar to baseline (p=0.74). Satisfaction levels of GI and GII were similar at baseline, 3 and 6 months, but GII showed higher satisfaction levels (p=0.01) than GI at 12 months. GI and GII exhibited a significant increase (p<0.05) in masticatory performance for all periods relative to baseline. However, GII had higher masticatory performance with dentures than GI, regardless of the period (p<0.05). Conclusion: MOD supported by two implants demonstrated better patient satisfaction in the follow-up at 12 months and better masticatory performance than MOD supported by one implant.